Comparison of tensiomyographic neuromuscular characteristics skeletal muscle properties in gymnasts - Atikovic, A.; Samardzija Pavletic, M.; Colakhodzic, E.; Petkovic, E.; Nozinovic Mujanovic, A.; Lilic, A.; Delaš Kalinski, S. (Journal of Physical Education and Sport, 2023)
Objective: The purpose of this study is a comparison of skeletal muscle characteristics in Slovenian gymnasts assessed by TMG and values of contraction properties of muscles, lateral symmetries, and the effect of aging on selected contraction properties of skeletal muscles in men's artistic gymnastics (MAG); women's artistic gymnastics (WAG) and rhythmic gymnastics (RG). This study is the first larger study to use the TMG method and in which top athletes from artistic and rhythmic gymnastics participated. Materials and Methods: A survey of 81 athletes from different disciplines was conducted as follows: MAG (n = 26), WAG (n = 28), and RG (n =27). The athletes` average age was 15.41 ± 5.03 years. In this study, the contraction times of ten skeletal muscles for Slovenian gymnasts on the right and left sides of the body were compared: M. Biceps brachii, M. Triceps brachii, M. Biceps femoris, M. Erector spinae, M. Gastrocnemius lateralis, M. Gastrocnemius medialis, M. Rectus femoris, M. Tibialis anteriror, M Vastus lateralis, M. Vastus medialis. Results: In MAG, a statistically significant correlation between age and contraction time was found for m. VL and m. VM. In WAG, was found for m. GM. In RG was found for m. TA and m VL for all at p < 0.01. Conclusions: A comparison between the left and the right side body shows a slight asymmetry. With TMG, we can assess the discipline`s demands and help improve gymnasts` performances along with the safety of training. Tensiomyography has a high predictive ability to discriminate between the left and right sides of the body functionally.